(untitled) (European Journal of Pure and Applied Mathematics, 2020)
In the present paper, we introduce the notions of Inf-hesitant fuzzy subalgebras and Inf-hesitant fuzzy ideals in BCK/BCI-algebras and investigate their relations and properties. In addition, we discuss the characterizations of Inf-hesitant fuzzy subalgebras and Inf-hesitant fuzzy ideals in BCK/BCI-algebras.